The role of body computed tomography in hospitalized patients with obscure infection: Retrospective consecutive cohort study. Issue 132 (November 2020) - Pohlan, Julian; Hernando, Maria Isabel Opper; Hogrebe, Anna; Witham, Denis; Muench, Gloria; Kwon, Ho Jung; Goehler, Friedemann; Marek, Andrea; Praeger, Damaris; Dewey, Marc
Highlights: Body CT detects 90 % of sources in the chest, abdomen and genitourinary tract in patients with obscure infection from general wards. Focus detection accuracy depends on the diagnostic confidence of the CT reader. The positive predictive value reaches 96.4 % (95 % CI 87.4%–99.1%) in cases with high diagnostic confidence. Clinical factors had higher prediction for CT findings than laboratory parameters. Abstract: Objective: Patients with severe infection or sepsis require fast identification of the focus and prompt eradication. This study aims at investigating the role of body computed tomography (CT) and identifying outcome predictors in a general ward setting of patients with obscure infection. Methods: We retrospectively identified 196 consecutive body CTs acquired in 179 patients with obscure infection, i.e. severe infection or sepsis from general wards with unclear focus, over 12-months in the year 2018. Reports were extracted using a full-text search in the radiological information system (RIS) of a large university medical center. CT reports were classified according to diagnostic confidence of the reader (i.e. certain, likely, possible, no focus), and correlated with clinical and laboratory parameters. The discharge diagnosis was set as the diagnostic reference standard. Contingency tables were prepared for statistical analysis with Chi-squared test amongst other analyses and the calculation of AUC statistics. Results: In 133 out of 196 (67.9 %) body CTs from general wards with severe infection or sepsis, body CT identified an infectious focus. 90 % of the infections were located in the chest, abdomen, and genitourinary tract, in descending order. In 76.5 % (150 of 196) of examinations, CT correctly predicted the final infectious source. The positive predictive value (PPV) of a CT-detected focus was 84.2 % (95 % CI 79.0%–88.3%). A high diagnostic confidence of the reader resulted in a PPV of 96.4 % (95 % CI 87.4%–99.1%) while a low confidence resulted in a PPV of 63.3 % (95 % CI 48.2%–76.3%). Conclusion: In patients with obscure infection treated in general wards, body CT detects the infectious source with a high positive predictive value. Focus detection accuracy highly depends on the diagnostic confidence of the CT reader.